Sliding mode control for the Frank–Starling response of a piston pump mock ventricle. (January 2015) - Gwak, Kwan-Woong; Kim, Hae Dong; Lee, Soon-Geul; Park, Sungsu; Kim, Chang-Wan
Highlights: Accurate reproduction of native ventricle's pumping dynamics. SMC to overcome high-bandwidth pressure dynamics and parameter uncertainties. Modeling and realization of hydraulic cardiovascular circulatory loop. Superior performance than FBL and PID. Confirmed physiological validity of cardiovascular circulatory simulator. Abstract: Accurate reproduction of native ventricular pumping dynamicsFrank–Starling responseis key for reliable in vitro cardiovascular circulatory simulators. However, due to high-bandwidth pressure dynamics, nonlinearity and model uncertainty of the mock ventricle often built with piston pump, it has been difficult to achieve accurate realization of Frank–Starling response. To overcome such difficulties, a sliding mode controller that is effective for the systems with fast dynamics and uncertainties is proposed in this research. Stability of the proposed controller is proved by Barbalat's lemma, and its performance is confirmed through experiments. Parameters of the controller is identified by fluidic elements modeling of the experimental system. The proposed controller is experimentally verified to be effective for various physiologic scenarios. Thanks to the high control performance, cardiovascular circulatory simulator yield a good match with the reference model behavior, and thereby physiological validity is secured.